BMT Nu Sidey's Strategy in Realized UMKM Financing with Sharia Economic Principles - al ishaqi, M. Afthon; Muhlis, Muhlis (PT. Anagata Sembagi Education, 2026)
The development of Micro, Small and Medium Enterprises (MSMEs) has a strategic role in the growth of the community's economy. One of the financial institutions based on sharia concepts that plays a role in empowering and prospering MSMEs is Baitul Maal wat Tamwil (BMT). The aim of this research is to determine the application of the sharia economic principles in building and developing MSMEs in the BMT NU Sidayu area. The research method used is a qualitative approach with data collection techniques through observation, interviews and documentation. The research results show that the application of sharia economic principles at BMT NU Sidayu is able to increase access to capital, business assistance, and the welfare of MSME players. A fair, transparent and partnership-based financing system is the main factor in encouraging the development of MSMEs in the region.